Extracellular volume fraction with MRI: As an alternative predictive biomarker to dynamic contrast-enhanced MRI for chemotherapy response of pancreatic ductal adenocarcinoma. Issue 145 (December 2021) - Fukukura, Yoshihiko; Kumagae, Yuichi; Fujisaki, Yosuke; Nakamura, Shinya; Dominik Nickel, Marcel; Imai, Hiroshi; Yoshiura, Takashi
Highlights: Extracellular volume (ECV) fraction is a useful biomarker for pancreas cancer. ECV fraction is correlated with K trans or ve determined by DCE-MRI. MR quantification of ECV fraction can be used in place of DCE-MRI. Abstract: Purpose: To assess the feasibility of extracellular volume (ECV) fraction determined with equilibrium contrast-enhanced MRI for prediction of treatment response to chemotherapy in pancreatic ductal adenocarcinoma (PDAC) in comparison with dynamic contrast-enhanced MRI (DCE-MRI), and to clarify the association between ECV fraction and DCE-MRI-derived pharmacokinetic parameters. Methods: This retrospective study included 58 consecutive patients with histologically confirmed PDAC who underwent DCE-MRI before systemic chemotherapy. Tumor pharmacokinetic parameters, including the volume transfer coefficient ( K trans ), rate constant ( kep ), and extracellular extravascular volume fraction ( ve ) of DCE-MRI, and ECV fraction determined with equilibrium contrast-enhanced MRI were compared between the response and non-response groups. The correlation of tumor ECV fraction with each DCE-MRI-derived pharmacokinetic parameter was examined using Spearman's rank correlation coefficient. Results: Tumor K trans, ve, and ECV fraction were significantly higher in the response group than in the non-response group (all, P  < 0.001), whereas no significant difference was found in kep ( P  = 0.119). Tumor ECV fraction showed the highest area under receiver operating characteristic curve of 0.918, with a sensitivity of 89.3%, specificity of 90.0%, and accuracy of 89.7% (cut off, >37.6%). The ECV fraction showed a significant positive correlation with K trans (Spearman's coefficient = 0.66, P  < 0.001) and ve (Spearman's coefficient = 0.79, P  < 0.001). Conclusions: ECV fraction determined with equilibrium contrast-enhanced MRI was as useful as DCE-MRI-derived pharmacokinetic parameters for predicting treatment response to chemotherapy in patients with PDAC.